Development of Augmented Reality-Based Multimedia for Enhancing Students' Understanding of Molecular Shapes - Deuit Widya; Bibin Rubini; Leny Heliawati (Didaktika: Jurnal Kependidikan, 2024)
This study is a research and development (R&D) project aimed at enhancing students' conceptual understanding after using Augmented Reality (AR)-based multimedia for molecular shape topics. The research and development design employed is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study was conducted from November 2021 to September 2023. The subjects for the implementation of the molecular shape multimedia were 36 students from the 10th grade of a senior high school with a science major. Data were collected through multimedia validation questionnaires, multiple-choice questions with explanations, students' conceptual understanding tests, and student response questionnaires. Multimedia validation was carried out by expert lecturers and Chemistry teachers. The results indicate that the AR-based molecular shape multimedia is valid and suitable for use in terms of feasibility (content, presentation, and language) with a feasibility percentage of 91.66%. The Content Validity Index (CVI) related to the feasibility of the multimedia is 0.995 (valid). Learning using AR-based molecular shape multimedia can improve students' conceptual understanding. Students' responses to the AR-based molecular shape multimedia were very good, with an average score percentage of 92%. This study concludes that there is an improvement in students' conceptual understanding after using the AR-based molecular shape multimedia.